THE EFFECT OF MICROWAVE HEATING ON THE PROTEIN CONTENT OF MUDSKIPPER (Periophthalmus minutes)FISH FLOUR - R. Fathul Rahman; Edison Edison; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to examine the effect of microwave heating on the protein content of mudskipper (Periophthalmus minutes) fish flour.The method used was experimental and composed as Completely Randomized Factorial Design (CRFD) by consists of 2 factors, namely factor A is the power with three treatment levels (A1400,A2 500, and A3600 watts) and factor B is time with 2 treatment levels (B150 and B260 minutes). Parameters tested include chemical composition testing, a yieldand physical appearance of fish flour. The results showed that thechemical composition inmudskipper meatwas 78,54% water (WW), 88,89% protein (DW) and 6,57% ash (DW). The Heating with the best treatment was A3B2 (600 watts, 60 minutes) with an 84,17% yield, 5,16% water (WW), 87,51% protein (DW), 6,19%ash (DW) and 53,17% total amino acid (DW). Power consumption and heating time in a microwave was different, indicating the physical appearance of flourfish with a fine texture, uniform and passed on a 60 mesh filter with the color of fish flour were brownish-yellow. The greater power and length of heating time using a microwave causes the color of flour to brown, but the color tends to affect the drying time. The longer of heating time using a microwave tends to darken of flour color. Keywords: Protein, mudskipper, microwave and flour.